2021
DOI: 10.1111/jocn.16125
|View full text |Cite
|
Sign up to set email alerts
|

Older adults' perceptions of their fall risk in the hospital: An integrative review

Abstract: Aims and Objectives:The objectives of this review are to determine what is currently known about older adults' perceptions of their own fall risk in the hospital and associated factors and explore how perceived fall risk in the hospital is assessed. Background: Every year, up to one million patients suffer an accidental fall in the hospital. Despite research efforts during the last decade, inpatient fall rates have not significantly decreased, and about one third of inpatient falls result in injuries. Limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…A major finding from this scoping review, in line with the first research objective, is the disparity between patients’ fall perceptions and their physiological fall risk in hospital. This also confirms the qualitative findings of Heng, Slade [ 6 ] and of Dolan, Slebodnik [ 69 ], in which participants were not aware of their risk of falling despite having multiple risk factors for falling. Although this mismatch of fall risk is established, only one instrument (Self-Awareness of Falls Risk Measure) directly measures the fall risk disparity from the validated fall perception measures.…”
Section: Discussionsupporting
confidence: 89%
“…A major finding from this scoping review, in line with the first research objective, is the disparity between patients’ fall perceptions and their physiological fall risk in hospital. This also confirms the qualitative findings of Heng, Slade [ 6 ] and of Dolan, Slebodnik [ 69 ], in which participants were not aware of their risk of falling despite having multiple risk factors for falling. Although this mismatch of fall risk is established, only one instrument (Self-Awareness of Falls Risk Measure) directly measures the fall risk disparity from the validated fall perception measures.…”
Section: Discussionsupporting
confidence: 89%
“…Given that hospital seems to be a new environment for patients in their 60s, this probably made them anxious and increased their self-perceived fall risk. 35 However, taking fall-related injuries into consideration, age appeared to be an insignificant factor. The mediating effect of fall-related injuries in the model may be attributed to this.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by their attitudes towards hospitalisation. Given that hospital seems to be a new environment for patients in their 60s, this probably made them anxious and increased their self-perceived fall risk 35. However, taking fall-related injuries into consideration, age appeared to be an insignificant factor.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reviews reported on adult inpatient perceptions of falls (Dabkowski et al, 2022; Dolan et al, 2022). These reviews highlight that the majority of participants did not consider themselves at risk for falling (Dabkowski et al, 2022; Dolan et al, 2022). Furthermore, prominent themes addressed participant concerns about self‐identity, dignity, autonomy and independence (Dabkowski et al, 2022).…”
Section: Introductionmentioning
confidence: 99%